IMPACT ANTHROPIQUE SUR LA QUALITE DES EAUX SOUTERRAINES DU BASSIN VERSANT DE L’OUED TAZA (MAROC) ANTHROPOGENIC IMPACT ON GROUNDWATER QUALITY IN THE WATERSHED OF OUED TAZA (MOROCCO) - Abbou, M. Ben; Fadil, F.; El Haji, M.; Zemzami, M. (European Scientific Journal, ESJ, 2014)
The main objective of this work is to determine the status of the groundwater quality in the watershed of Taza river, based primarily on physico-chemical and bacteriological parameters of groundwater. The Oued Taza is a small mountain river, 13.44 Km long, which drains a watershed of 40.07 km ². The outlet located at an altitude of 420 m corresponds to the confluence with the Oued Iarbaa. The average annual rainfall varies between 352 mm and 719mm while the annual average temperature is 18.1 ° C. Very high concentrations of nitrates, nitrites, heavy metals and bacterial load in some points near urban areas, illustrate the effect of human activities on degradation of water quality. This contamination could have several causes, the most important are related to household and industrial discharges (especially waters) spilled without any treatment in the rivers, and the use of fertilizers in agricultural areas. These results will enrich the database on water quality in the basin, and help policy makers to better decide on the management of water resources for a better sustainable development of the region